43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-1098
|View full text |Cite
|
Sign up to set email alerts
|

Role of Turbulent Prandtl Number on Heat Flux at Hypersonic Mach Numbers

Abstract: A new turbulence model suited for calculating the turbulent Prandtl number as part of the solution is presented. The model is based on a set of two equations: one governing the variance of the enthalpy and the other governing its dissipation rate. These equations were derived from the exact energy equation and thus take into consideration compressibility and dissipation terms. The model is used to study two cases involving shock wave/boundary layer interaction at Mach 9.22 and Mach 5.0. In general, heat transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This difficulty is characteristic of turbulence models that base the turbulent heat-flux vector on Reynolds' analogy. As shown by Xiao et al [58], realistic predictions for hypersonic reattachment point heat transfer can be achieved by constructing additional model equations to compute the heat-flux vector.…”
Section: E Mach 11 Reflecting Shockmentioning
confidence: 99%
“…This difficulty is characteristic of turbulence models that base the turbulent heat-flux vector on Reynolds' analogy. As shown by Xiao et al [58], realistic predictions for hypersonic reattachment point heat transfer can be achieved by constructing additional model equations to compute the heat-flux vector.…”
Section: E Mach 11 Reflecting Shockmentioning
confidence: 99%
“…Authors would like to emphasize that Pr t = 9 is specifically considered in the near-wall region and this value decreases away from the wall. It is noteworthy to highlight the work of Xiao et al [17], who developed a new turbulence model suited to calculate the turbulent Prandtl number as part of the solution at hypersonic Mach numbers. This two-equation model has shown significant improvement in the wall heat flux prediction over traditional turbulence models where the Pr t is assumed constant.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies [31, for example] have shown an extreme sensitivity of RANS calculations to the choices of the turbulent Prandtl and Schmidt numbers. While models exist to calculate the variation of these quantities as part of a RANS solution [32,33], their development has been hampered by the lack of detailed experimental data for the turbulent scalar fluxes. One of the advantages of a large-eddy simulation approach is that larger-scale transport mechanisms are directly captured, and given a large-eddy simulation (or hybrid LES/RANS) database, it is possible to extract Favre-averaged distributions of fluxes of mass, momentum, and energy due to turbulent fluctuations and to compare them with Boussinesq / gradient-diffusion closures commonly used in RANS modeling.…”
Section: E Calculation Of Turbulent Prandtl and Schmidt Numbersmentioning
confidence: 99%